Legendre polynomial order selection in projection pursuit density estimation - Kavaliauskas, Mindaugas (Lietuvos matematikos rinkinys, 2013)
Projection pursuit method and its application to probability density estimation is discussed. Method proposed by J.H. Friedman, based on projection density estimation using orthogonal Legendre polynomials, is analysed. Problem of Legendre polynomial order selection is solved. Conclusions are based on Monte Carlo simulation.
Keywords: projection pursuit; probability density; nonparametric estimation